Propuesta mejoramiento control interno al área de cartera de la copropiedad zona franca del pacifico. - Sánchez González, Liceth Fernanda (Universidad Antonio Nariño, 2022)
Pacific Free Zone with morethan 25 years of experience located in the city of Palmira is a private industrial and logistics park with tax and customs benefits for industrial, logistics and commercial projects.